Histone deacetylases mediate the silencing of miR-15a, miR-16, and miR-29b in chronic lymphocytic leukemia - Sampath, Deepa (American Society of Hematology, 2012)
Chronic lymphocytic leukemia (CLL) demonstrates a global down-regulation of miR-15a and miR-16 and a selective silencing of the related miR-29b in aggressive disease. Deletions in chromosome 13 [del(13q14)] partially account for the loss of expression of miR-15a and miR-16, but the mechanisms by which miR-29b becomes silenced is unknown. In the present study, we show that the histone deacetylases (HDACs) are overexpressed in CLL and mediate the epigenetic silencing of miR-15a, miR-16, and miR-29b. HDAC inhibition triggered the accumulation of the transcriptionally activating chromatin modification H3K4me2 and restored the expression of miR-15a, miR-16, and miR-29b in approximately 35% of samples. Ectopic expression of miR-15a and miR-16 and HDAC inhibition–induced expression of miR-15a, miR-16, or miR-29b in primary CLL cells was associated with declines in the levels of Mcl-1, but not Bcl-2, mitochondrial dysfunction, and induction of cell death. Therefore, our results show that HDACs aberrantly silence the expression of the critical tumor suppressors miR-15a, miR-16, and miR-29b in CLL. Deacetylase inhibition may be a therapeutic strategy that restores the expression of these miRs to antagonize Mcl-1, an important survival protein in these cells. Consequently, CLL patients who exhibit such epigenetic silencing may benefit from HDAC inhibitor–based therapy.